Konstrukcja stanu wyższej konieczności w projekcie polskiego kodeksu karnego z 1932 roku - Pasek, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article is devoted to state of necessity in the draft Polish Criminal Code of 1932. The author discusses the origins of the construct, its place in the criminal codes in force in Poland, the work of the Criminal Law Section of the Codification Commission of the Polish Republic, and the legal structure of the regulations in the draft Polish Criminal Code. He demonstrates that the state of necessity in the draft Polish Criminal Code of 1932 was shaped by in-depth reflection in the Criminal Law Section taking into account the European doctrine of law and European legislation. When it comes to the state of necessity, the draft Polish Criminal Code sought to apply to it the latest solutions known from the existing legislation
Keywords: prawo karne; projekty aktów prawnych; stan wyższej konieczności; Makarewicz Juliusz (1872-1955)